La Producción de Lechuga en Sistemas Hidropónicos a Pequeña Escala - German V. Sandoya; Jonael Bosques; E. Vanessa Vassilaros (EDIS)
This publication presents an overview on the use of different small hydroponic systems that could be implemented by home gardeners. Recommendations on lighting, media, and other key aspects are presented in this publication as well. Spanish translation of HS1422, Growing Lettuce in Small Hydroponic Systems, by Germán V. Sandoya, Jonael Bosques, and E. Vanessa Vassilaros. Published by the UF/IFAS Horticultural Sciences Department; 8 pp.